Association between urinary concentration of phthalate metabolites and impaired renal function in Shanghai adults. (February 2019) - Chen, Jingsi; Zhou, Xiaofeng; Zhang, Han; Liu, Yueming; Cao, Chen; Dong, Ruihua; Yuan, Yaqun; Wang, Min; Lu, Yuanan; Wu, Min; Li, Shuguang; Chen, Bo
Abstract: Background: Exposure to phthalates is reported to be associated with increased incidence of microalbuminuria and low-grade albuminuria in children and adolescents. However, this phenomenon of phthalate-related nephrotoxicity is unknown in adults. Methods: Urine samples of 1663 adults from the 2012 Shanghai Food Consumption Survey (SHFCS) were measured for 10 metabolites of 6 phthalates and for renal function parameters. Their associations were explored by linear and logistic regression models. Results: Multivariate linear regression analysis showed that all three renal function parameters (albumin-to-creatinine ratio (ACR), β2-microglobulin (B2M), and N-acetyl-β-d-glucosaminidase (NAG)) are positively associated with six metabolites, including mono-benzylphthalate (MBzP), mono-2-ethylhexylphthalate (MEHP), mono-2-ethyl-5-oxohexyphthalate (MEOHP), mono-2-ethyl-5-hydroxyhexylphthalate (MEHHP), mono-2-ethyl-5-carboxypentylphthalate (MECPP), and mono-2-carboxymethyl-hexyl phthalate (MCMHP) ( P < 0.05). Logistic analysis showed that the prevalence of hyperALBuria, hyperB2Muria, hyperNAGuria, or potentially impaired renal function (PIRF) were positively associated with urinary levels of MBzP, MEOHP, and MECPP, respectively ( P < 0.05). Co-exposure to identified risk metabolites monoethylphthalate (MEP), MBzP, MEHP, MEOHP, MECPP, MEHHP, and MCMHP increased the risk of having impaired renal function. Conclusion: Certain metabolites of phthalates, including bis (2-ethylhexyl) phthalate (DEHP) and benzyle butyl phthalate (BBzP), were associated with impaired renal function in Shanghai adults. Graphical abstract: Highlights: Phthalate nephrotoxicity in community adults was reported for the first time. Urinary metabolites of phthalates (mainly DEHP and BBzP) was positively associated with all impaired renal function. Albumin-to-creatinine ratio, β2-microglobulin, and N-acetyl-β-d-glucosaminidase were affected by phthalate exposure. Abstract : Not only albuminuria but also other renal function parameters (B2M and NAG) are associated with increased excretion of phthalate metabolites in urine.